P03 The use of BRUM1 resequencing microarray to identify mutations in patients with neonatal cholestasis. (16th November 2010) - Hartley, J; Bruce, C; Brown, R; McKay, K; Bauman, U; Sturm, E; Udd, B; Mckiernan, P; McMullen, D; Mansson, J; McDonald, F; Maher, E; et al.
Abstract : Introduction: Neonatal cholestasis is the presenting clinical feature of serious and potentially life limiting liver diseases such as progressive familial intrahepatic cholestasis (PFIC), arthrogryposis-renal-cholestasis (ARC) syndrome and Niemann Pick C (NPC) disease. A single rapid molecular test to confirm the diagnosis would reduce the delay from molecular genetic investigation at multiple diagnostic centres thus facilitating optimal clinical management and counselling. We have designed a resequencing microarray (BRUM1) capable of simultaneously sequencing multiple genes associated with neonatal cholestasis. Aim: To assess the utility of BRUM1 as a first-line molecular investigation for patients with neonatal cholestasis in whom an inherited causes is suspected. Method: DNA from 95 infants with neonatal cholestasis in whom an inherited cause was suspected was amplified by PCR and hybridised to BRUM1 (validated against reference sequencing with 98.9% agreement (CI 0.97 to >0.99)) for simultaneous sequencing of the main causes of inherited disease in this group which included ATP8B1, ABCB11, ABCB4, VPS33B, VIPAR, NPC1 and NPC2. Children with known α-1 antitrypsin deficiency or Alagille syndrome were not included. Results: 30 infants had pathogenic mutations, which cause neonatal cholestasis. 23 of the mutations were novel. Abstract P03 Table 1 Results Gene Total number of mutations Novel mutations ATP8B1 6 1 ABCB11 11 10 ABCB4 2 1 VPS33B 5 4 VIPAR 2 2 NPC1 17 4 NPC2 1 1 In this cohort of patients, 30.5% of infants with neonatal cholestasis had a genetic diagnosis confirmed by BRUM1. The average time to diagnosis was 5–25 days. Conclusion: A specific and rapid genetic diagnosis in infants with a phenotype of neonatal cholestasis can be made using a single resequencing microarray, to optimise clinical management and facilitate appropriate counselling of families.